THE EFFECT OF PARTICLE SIZE AND COMPACTING FORCE TO POROSITY, COLD CRUSHING STRENGTH, AND WEAR RESISTANT OF ALUMINA SPINEL REFRACTORIES - KHOIRUL AMRI (NIM : 12512048), FUAD
The world demand of refractory increase every year. It is caused by the rising of the worldÃ‚Â’s steel production. Steel industry consume about 60% of the producted refractory. One of the refractory that used by the steel industry is magnesia-alumina spinel. These kind is used on rotary kiln and slide gate at the ladle. This application needs refractory with good refractoriness. The particle size and the compacting force affect the physical and mechanical properties of refractory. The research on the effect of particle size and compacting force on physical and mechanical properties of refractory is still hardly ever. This research varying the size of the particle and the compacting force in it. The particle size variable is obtained from the available grain enrichment, i.e. -3# +4#, -4# +6#, -6# +8#, -8#, and +10# for coarse fraction, then -14#, +20#, -20# +30#, and -30# for the medium size. Another substances which is added are fine fraction, graphite as much as 10%, aluminium powder as much as 5%, and phenolic resin as the binder as much as 5%. Meanwhile, pressure force variable is fixed on 10 kN, 30 kN, 50 kN, and 70 kN. The conducted test covers the porosity test, bulk density test, cold crushing strength test, and wear-resistant test. The other test that also conducted are XRD and SEM/EDS characterization. The research result showed that the smallest value of the porosity test is 26,50%. This result is gained when the size variation is -8# and +10# for coarse fraction, then -30# for medium-size fraction at 70 kN compacting force. The highest value of the bulk density is gained when the size variation is 3# +4# for coarse fraction, then -14# for medium-size fraction with compacting force at 70 kN, i.e. 2.49 gr/cm3. The highest value of the cold crushing strength is gained when the size variation is at -6# +8# for the coarse fraction, -20# +30# at medium-size fraction, and 70 kN compacting force, i.e. 30,43 MPa. The best wear-resistance value is obtained when the coarse fraction is at -6# +8#, the medium-size fraction at -20# +30#, and compacting force at 70 kN, i.e., 0,00084 grams/minutes. In XRD test, it is shown that alumina and spinel are the phases formed. Meanwhile, in SEM/EDS test, it is shown that there is a leftover graphite and there is a forming of aluminum carbide which is affects the refractory properties.